Report and lament – Zalman Gradowski’s notes from Auschwitz - Adamczyk, Kazimierz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The notes by Zalman Gradowski, one of the leaders of the rebellion of the Sonderkommando in Auschwitz-Birkenau, are one of the most important Holocaust documents created by its victims right from its epicentre as the crime progressed. Their fragments were published in Poland and Israel. Gradowski was a religious Jews from Grodno. At the camp, he prayed every day, and wrote down details of each transport. His family: mother, wife, and children, were murdered in the gas chambers immediately upon arriving at Auschwitz. The author of the article analysed the literary value of this exceptional document, which consists of diary notes of a narrative nature, and evocative lyrical passages being a discussion with God deeply rooted in Judaic traditions. Thus, one reads an account of the nature of a report and lament. That exceptional – given its place of origin and literary value – record of the crime, and the suffering of the victims of the Holocaust urges one to ask once more about the inexpressibility of Shoah.